Comparative Formants Analysis of English Vowels Using PRAAT - Sekar Azzahra; Tengku Syarfina; Franinta Egia D. R Br Sembiring (UIBU, 2024)
This research focuses on the comparative formant analysis of English vowels between native and non-native speakers using PRAAT software. The study aims to investigate the comparison of the acoustic properties of English vowels to understand the pronunciation differences encountered by non-native speakers. By analyzing the formant frequencies of monophthongs in English vowels, specifically the first formant (F1), this research seeks to identify any significant differences between English native speaker and five non-native speakers, whose first language is Indonesia. The data collected from speech samples will be descriptively analyzed to determine variations in formant patterns. The finding shows that the F1 values of the vowels show variations among the non-native speakers compared to the native speaker. There are still monophthongs that these participants mispronounce, indicating that the learner's understanding is an obstacle to their fluency in speaking and pronouncing the sounds correctly. The research findings imply that these mispronunciations are linked to differences in tongue height, vowel backness, and vowel quality between native and non-native speakers. The results underscore the analysis of F1 values for 12 words containing vowel monophthongs, highlighting these variations. This suggests that the learner's understanding of these phonetic aspects is crucial for achieving fluency in vowel production and pronunciation.